Proceedings of the 3rd ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2017) 2018
DOI: 10.2991/acpch-17.2018.40
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self-Efficacy and Gender on The Work-Family Balance of Employees in Yogyakarta

Abstract: Abstrack. This research paper aims to discover the effects of self-efficacy and gender on the work-family balance levels of employees working in Yogyakarta. The research subjects consisted of 76 employees, half of them are male and the other half are female, working in both public and private sectors. The methods used in this research are quantitative methods. The data was collected by using two scales, which are work-family balance scales and self-efficacy scales. The chosen data analysis technique in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Manufacturing companies' employees with sufficient belief in their capacity to plan and execute tasks at work and family domains are most likely to attain adequate balance. Past studies (Situmorang & Wijayanti, 2017;Cetin & Askun, 2019) reported that individuals with a high level of selfefficacy will have confidence in their abilities to properly handle work and family demands. When employees trust their ability to deliver their roles and work, it may likely prevent spillover effects which may, in turn, have negative effects on the demands that family responsibilities might be placed on them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturing companies' employees with sufficient belief in their capacity to plan and execute tasks at work and family domains are most likely to attain adequate balance. Past studies (Situmorang & Wijayanti, 2017;Cetin & Askun, 2019) reported that individuals with a high level of selfefficacy will have confidence in their abilities to properly handle work and family demands. When employees trust their ability to deliver their roles and work, it may likely prevent spillover effects which may, in turn, have negative effects on the demands that family responsibilities might be placed on them.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of work, self-efficacy has been found to be related to other work outcomes such as job satisfaction, work engagement, and turnover intention (Yakin & Erdil, 2012;Ozyilman, Erdogan, & Karaeminogullari, 2018), as well as work performance (Celtic & Askun, 2019). Also, individuals with a high level of self-efficacy are most likely to have confidence in their capacity to properly handle demands from their workplaces and families (Sweetman & Luthans, 2010;Situmorang & Wijayanti, 2017). Based on this position in literature, the study hypothesized that self-efficacy will positively relate to work-family balance among employees in manufacturing companies.…”
Section: Self-efficacy and Work-family Balancementioning
confidence: 99%
“…However, the hope, the other PsyCap component found insignificant in affecting the WLB (β = 0.101911, 0.062). Yet, several existing findings support a positive connection between these two variables concerning different contexts (Situmorang & Wijayanti, 2018;Duggleby, et al, 2009). The inconsistency in the results can be attributable to the routine nature of the join apparel sector and also the limited career paths for further development.…”
Section: Table 4: Path Coefficients and Their Significancementioning
confidence: 95%
“…These significant associations were further confirmed by the similar findings of the previous studies. Positive imaginations backed by optimism help employees to be happy with the present level of the job and as well as the future accomplishments they expected (Situmorang & Wijayanti, 2018). Then, this would play a big role in balancing the demands of work and family lives.…”
Section: Table 4: Path Coefficients and Their Significancementioning
confidence: 99%
“…Despite the large number of studies on self-efficacy, its relationship with work-life balance has not received adequate attention in the literature (Badri & Panatik, 2020). Few studies have confirmed that self-efficacy impacts work-life balance (Siu, 2013;Polatçı & Akdoğan, 2014;Nina & Fauziah, 2017;Kaplan, 2018;Badri & Panatik, 2020;Akkuş, Najimudinova & Gül, 2020;Parray, Shah & Islam, 2022).…”
Section: Introductionmentioning
confidence: 99%